Integrating Content and Language to Teach ESP Online Writing with the Assistance of Google Docs - Susilawati, Susilawati (Universitas Pendidikan Mandalika, 2023)
The integration of content knowledge and language should be applied while instructing writing in English for Specific Purposes (ESP) lessons. In an online lesson, additional vital support comes from a proper online writing tool. Therefore, the present study aims to portray how to teach writing in ESP classes using remote Content and Language Integrated Learning (CLIL) combined with Google Docs as an online writing tool. The study employed a qualitative case study. 18 students from the Office Administration major at a private Indonesian university in Central Jakarta were involved in the study. Observations and open-ended questionnaires were used to collect the data. The observations were structured based on the writing stage, while the open-ended questionnaires were arranged based on the Uses and Gratification Expectancy (UGE) constructs. The findings revealed that all CLIL elements are applied to teach ESP writing in a full online learning setting; all 4Cs (communication, culture, content, and cognition) are detected during the learning either before or during the writing via Google Docs. Pertaining to the use of Google Docs, based on the cognitive, affective, personal, and perceived e-learning (PeLE) constructs of the UGE, most students give positive views after using it in their writing classes. In short, CLIL and Google Docs make a good collaboration in teaching ESP writing. Recommendations for potential research are also discussed.Â